Hubungan Nilai Ujian Try Out Lokal dengan Nilai Computer Based Test Uji Kompetensi Mahasiswa Program Profesi Dokter di Fakultas Kedokteran Universitas Sam Ratulangi Manado - Labatjo, Atika I. S.; Manoppo, Firginia P.; Berhimpon, Siemona L. E. (Universitas Sam Ratulangi, 2019)
Abstract: The graduation rate of the Computer Based Test (CBT) in Competency Test for Medical Student Profession Program (UKMPPD) of Medical Faculty, Sam Ratulangi University is still below 50% so far. Therefore, the Medical Faculty of Sam Ratulangi University makes various efforts to increase their graduation rate, inter alia implementation of local Try Out (TO) test as a filtering test required before the CBT UKMPPD. This study was aimed to find out whether there was a correlation between the local TO test score and the CBT UKMPPD score. This was a descriptive analytical study with a cross-sectional design. Data of this study were the local TO test score and the CBT UKMPPD score of the Medical Faculty of Sam Ratulangi University. The data were analyzed with the Spearman correlation test. The results showed that there was a significant correlation (P=0.028) between the local TO test score and the CBT UKMPPD score with a very weak positive correlation value (r= 0.199). Conclusion: There was a significant correlation between the local TO test score and the CBT UKMPPD score.Keywords: TO, CBT, UKMPPDÂ Abstrak: Angka kelulusan Computer Based Test (CBT) Ujian Kompetensi Mahasiswa Program Profesi Dokter (UKMPPD) Fakultas Kedokteran Universitas Sam Ratulangi (FK Unsrat) Manado masih berada di bawah 50%. Pihak FK Unsrat melakukan berbagai upaya agar angka kelulusan UKMPPD FK Unsrat meningkat, salah satunya yaitu dengan mengadakan ujian Try Out (TO) lokal sebagai ujian penyaring yang wajib diikuti sebelum CBT UKMPPD. Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan antara nilai ujian TO lokal dengan nilai CBT UKMPPD. Jenis penelitian ialah deskriptif analitik dengan ddesain potong lintang. Data penelitian ialah nilai ujian TO lokal dan CBT UKMPPD FK Unsrat. Data dianalisis menggunakan uji korelasi Spearman. Hasil penelitian mendapatkan hubungan bermakna (P=0,028) antara nilai ujian TO lokal dengan nilai CBT dengan tingkat keeratan positif yang sangat lemah (r=0,199). Simpulan: Terdapat hubungan bermakna antara nilai ujian TO lokal dengan nilai CBT UKMPPD.Kata kunci: TO, CBT, UKMPPD